PENGARUH PENAMBAHAN EKSTRAK CINCAU POHON (Premna oblongifolia Merr.) PADA PAKAN TERHADAP KANDUNGAN BAKTERI ASAM LAKTAT DIGESTA DAN EFEK LAKSATIFNYA PADA TIKUS PERCOBAAN - Murhadi, Murhadi; Nurdin, Samsu Udayana; Aprizal, Dedy; Maryanti, Maryanti (Jurnal Teknologi & Industri Hasil Pertanian, 2009)
Dietary fiber with a high fermentability can be considered as prebiotic.  Inulin and Fructo-ligosaccharides has been well known as prebiotic resources. Dietary fibre with lower fermentability has a better laxative effect. Green cincau (Premna oblongifolia Merr.) as one of dietary fibre that contains pectin as it’s main gel forming agent. The previous study showed that pectin has a prebiotic function because it could increase beneficial bacteria level in digestion system with fermentability between 50% to 100%. The objective of this research was to compare the prebiotic function of  green cincau’s gel forming agent extract in increasing the lactic acid bacteria and it’s laxative effect (faecal proportion and faecal consistency) with a commercial prebiotic resource (inulin). This research was designed in a completely randomized block design, with a single treatment (different fiber resource added to the diets : green cincau’s gel forming agent extract, inulin, and selulose)). The results showed that green cincau’s gel forming agent extract has a lower prebiotic function but has a higher laxative effect if compared to commercial prebiotic (inulin) with total lactic acid bacteria  was 11.97,   the pH of the digesta was  6.27, and fecal proportion was 6.296%.